1983
DOI: 10.1159/000173580
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angiographic Features in Endomyocardial Fibrosis

Abstract: Selective coronary cineangiography was performed in 24 patients with angiographic features suggestive of endomyocardial fibrosis (EMF). 8 patients had right ventricular disease, 2 had left ventricular disease and 14 had biventricular disease. The abnormal features found in the coronary arteries of these patients were: (a) vascular blush or neovascularity in 54.2% of patients and (b) localized ventricular filling from the region of the blush in 16.7%. Generalized tortuosity of the coronary arteries, considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
1
3
0
1
Order By: Relevance
“…This however, collaborates the pathological criterion of differentiating rheumatic heart diseases from EMF (36,37). As already described and reported in the literature (38,39), diagnostic coronary cineangiocardiography in our study, demonstrated the typical ventricular deformities of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…This however, collaborates the pathological criterion of differentiating rheumatic heart diseases from EMF (36,37). As already described and reported in the literature (38,39), diagnostic coronary cineangiocardiography in our study, demonstrated the typical ventricular deformities of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…However, since we could not perform anatomicopathological study, the aetiology of the extensive myocardial calcification in this patient could not be identified. Balakrishnan et al [17] has been reported that abnormal features found in the coronary arteries of patients with EMF were vascular blush or neovascularity in 54.2% of patients, localized ventricular filling from the region of the blush in 16.7% and generalized tortuosity of the coronary arteries in 50%. In our patient, coronary artery obstruction probably due to calcification was also an interest finding.…”
Section: Discussionmentioning
confidence: 99%
“…Chest pain was present in 50% of the patients studied, sometimes during the follow-up, all of them presenting left ventricular disease. Balakrishnan et al described "blush" (or neovascularization) in the terminal coronary circulation in 54.2% of patients, using coronary cineangiocardiography [37]. This image might correspond to the vascular lesions described above since it is not present in healthy individuals with preserved terminal coronary circulation.…”
Section: Discussionmentioning
confidence: 98%